2018
DOI: 10.1103/physrevlett.121.058003
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Vitrimers: Defects as a Highway to Stress Relaxation

Abstract: We propose a coarse-grained model to investigate stress relaxation in star-polymer networks induced by dynamic bond-exchange processes. We show how the swapping mechanism, once activated, allows the network to reconfigure, exploring distinct topological configurations, all of them characterized by complete extent of reaction. Our results reveal the important role played by topological defects in mediating the exchange reaction and speeding up stress relaxation. The model provides a representation of the dynami… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
136
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(141 citation statements)
references
References 39 publications
5
136
0
Order By: Relevance
“…2(e). This effect is not surprising, as enhanced vitrimeric functionality is known to lead to more efficient relaxation and more liquid-like behavior D R A F T (37,51). Interestingly, we find that the fragility index m along the glass transition line is virtually unaffected by our choice of ∆Eswap ( Fig.…”
Section: Resultsmentioning
confidence: 53%
See 1 more Smart Citation
“…2(e). This effect is not surprising, as enhanced vitrimeric functionality is known to lead to more efficient relaxation and more liquid-like behavior D R A F T (37,51). Interestingly, we find that the fragility index m along the glass transition line is virtually unaffected by our choice of ∆Eswap ( Fig.…”
Section: Resultsmentioning
confidence: 53%
“…Compared to Ref. (37), the model was optimized in order to avoid its rigidification at the topological transition Tv (3) by changing the mixture ratios to reduce the number of intra-star bonds. In this condition, the mechanism driving the dynamical arrest is the standard glass transition, so that the system can relax and reach equilibrium even below Tv.…”
Section: Methodsmentioning
confidence: 99%
“…Analogous studies aimed at understanding the effect of crosslink kinetics on viscoelastic material responses have been performed for a number of synthetic polymeric materials. Besides investigating the effect of the crosslink properties themselves (Yount et al, 2005;Shen et al, 2007;Appel et al, 2014;Rossow et al, 2014;Grindy et al, 2015;Tunn et al, 2018), these studies have focused on the contributions of network defects such as dangling ends and loops (Annable et al, 1993;Rossow et al, 2014;Ciarella et al, 2018), crosslink functionality (Li et al, 2016;Gu et al, 2018;Tunn et al, 2019) and polymer length (Annable et al, 1993;Tan et al, 2017). Even though a direct comparison is difficult due to the different polymers used, it can generally be concluded that the number of elastically active chains and their ability to relax after crosslink dissociation are key parameters that determine the macroscopic relaxation time of a material.…”
Section: Introductionmentioning
confidence: 99%
“…5,6,23,24,25,26 Theoretical models have been developed to clarify the relationship between the exchange reaction kinetics and resulting vitrimer material characteristics. 27,28,29,30,31,32 While much of the vitrimer literature focuses on optimizing exchange reactions, diversifying polymer backbones, and applications, 33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49 less attention has been directed towards exploring incompatibility effects. This question should be particularly important in vitrimer systems, for example, in which the crosslink functional groups and network strands have very different polarizabilities.…”
mentioning
confidence: 99%